Application of multidisciplinary team conference for neuromodulation candidates facilitates patient selection and optimization - Salmasi, Vafi; Rasouli, Mohammad Reza; Kao, Ming C.; Ottestad, Einar; Terkawi, Abdullah Sulieman; Morris, Garret; Qian, Xiang; Coleman, Stephen; Talavera, David C.; Poupore-King, Heather; Slater, Kristen; Leong, Michael S. (Frontiers in Pain Research, 2024)
Introduction Psychological evaluation is required by insurance companies in the United States prior to proceeding with a spinal cord stimulation or a dorsal root ganglion stimulation trial. Since January 2017, we implemented a Multidisciplinary Team Conference for Neuromodulation in our center to facilitate the collaboration between pain physicians and psychologists and to optimize screening of neuromodulation candidates. This study aims to report the impact of this team conference on improvement of neuromodulation outcome in our center. Methods Appropriateness of neuromodulation were discussed in the team conference after initial visit with the pain specialist and psychological evaluation. For this study, we prospectively and retrospectively collected data on neuromodulation candidates who went through the team conference and those who did not as controls. Results We discussed 461 patients in the team conference sessions from January 2017 to July 2023. Out of these, a spinal cord stimulator or a dorsal root ganglion stimulator trial was performed in 164 patients with 80.5% (132 cases) trial success rate leading to 140 implants. Out of these implants, 26 (18.6%) explanted and 21 (15%) required revision in 41 (29.3%) patients. We performed neuraxial neuromodulation trial for 70 patients without going through the team conference from January 2016 to July 2023 with a trial success rate of 45.7% (32 cases). In this group, 7 (21.9%) and 6 (18.8%) patients underwent explant and revision. The differences between the groups were statistically significant for trial success rate (odds ratio of 4.9 with p-value of <0.01) but not for explant (odds ratio of 0.8 with p-value of 0.627) or revision (odds ratio of 0.8 with p-value of 0.595). Conclusion Implementing Multidisciplinary Team Conference increased trial success rate in our center. Team conference provides therapeutic benefit for patients, and also provides the opportunity for an educational discussion for trainees.